1998
DOI: 10.1023/a:1008469212268
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of gemcitabine in platinum pre-treated patients with advanced epithelial ovarian cancer

Abstract: Single-agent gemcitabine is active and well tolerated in patients with recurrent ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(61 citation statements)
references
References 13 publications
1
60
0
Order By: Relevance
“…In a small study of chemonaive patients, single-agent gemcitabine produced a modest overall response rate of 18% (D'Agostino et al, 2003). In patients with platinumpretreated, relapsed ovarian cancer, response rates ranged from 13 to 28%, which are comparable with those of other agents (e.g., topotecan, liposomal doxorubicin, and paclitaxel) in a similar patient population (Lund et al, 1994;Shapiro et al, 1996;Friedlander et al, 1998;Silver and Piver, 1999;von Minckwitz et al, 1999;Underhill et al, 2001). Gemcitabine is generally well tolerated with common toxicities including myelosuppression, lethargy, flu-like symptoms, peripheral oedema, and skin rashes.…”
mentioning
confidence: 91%
“…In a small study of chemonaive patients, single-agent gemcitabine produced a modest overall response rate of 18% (D'Agostino et al, 2003). In patients with platinumpretreated, relapsed ovarian cancer, response rates ranged from 13 to 28%, which are comparable with those of other agents (e.g., topotecan, liposomal doxorubicin, and paclitaxel) in a similar patient population (Lund et al, 1994;Shapiro et al, 1996;Friedlander et al, 1998;Silver and Piver, 1999;von Minckwitz et al, 1999;Underhill et al, 2001). Gemcitabine is generally well tolerated with common toxicities including myelosuppression, lethargy, flu-like symptoms, peripheral oedema, and skin rashes.…”
mentioning
confidence: 91%
“…This may lie on multiple factors. First, some studies strictly included only patients with platinum-free interval <6 months (platinumresistant) when the RRs were only 6-18% ( DOI:http://dx.doi.org/10.7314/APJCP.2014.15.13.5215 Treatment Outcomes with Gemcitabine for Refractory or Recurrent Ovarian Cancer others included heterogeneous group of patients with platinum-free interval ranging from <6 months or <12 months altogether when the RRs were 12-29% (Shapiro et al, 1996;Friedlander et al, 1998;D'Agostino et al, 2003;Ferrandina et al, 2008;Suprasert et al, 2012;Yoshino et al, 2012). Second, the status of platinum-resistance in these studies may be primary after first-line platinum drug or secondary after platinum re-induction.…”
Section: Discussionmentioning
confidence: 99%
“…Third was the regimen of gemcitabine. Some studies found RRs of 6-29% from single agent (Shapiro et al, 1996;Friedlander et al, 1998;D'Agostino et al, 2003;Markman et al, 2003;Mutch et al, 2007;Ferrandina et al, 2008;Watanabe et al, 2008;Suprasert et al, 2012;Yoshino et al, 2012) while others could demonstrate RRs of 13-70% from gemcitabine in combination with platinum or other agents (Greggi et al, 2001;Sehouli et al, 2002;Nagourney et al, 2003;Rose et al, 2003;Garcia et al, 2004;Papadimitriou et al, 2004;Ferrandina et al, 2005;Brewer et al, 2006;Pfisterer et al, 2006;Poole et al, 2006;Bozas et al, 2007). Another reason which might be under-recognized was the setting when gemcitabine was used or numbers of prior chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of chemotherapy options including liposomal doxorubicin [81], topotecan [81], etoposide [82,83], and gemcitabine [84,85]. The reported response rates are low, about 10%, with a median time to progression of 3-4 months and a median survival of 9-12 months.…”
Section: Chemotherapy For Recurrent Epithelial Malignanciesmentioning
confidence: 99%